NREGS As Instrument of Gender Mainstreaming: An Exploratory Analysis. - Viswanathan, P.K. and Mandal, Amit (2012)
This paper examines the case of National Rural Employment Guarantee Scheme (NREGS) implementation with respect to its gender dynamism across the Indian states. Based on the national level data on implementation of the Scheme, it examines the status of implementation of NREGS across states and brings out that the states have shown clear patterns of gender work participation in the NREGS. Accordingly, a handful of states (such as Kerala, Tamil Nadu, Rajasthan and Andhra Pradesh) continue to show extremely high levels of women work participation. About a dozen of states have shown moderate levels of gender work participation, while the majority of the states still lags behind in terms of gender work participation. The paper suggests that the lower levels of women participation in these states could be attributed to the interplay of several socio-economic, institutional, political and cultural factors, besides the possible structural issues of the NREGS that limits engagement of women in NREGS activities. Further, the states showing lower levels of women participation in the NREGS are also found lagging behind in terms of most of the gender development indicators with significant variations in between. However, empirical investigations using micro level data are still lacking in order to throw more useful insights in this regard. The paper also underlies the need for scaling up of the NREGS as an effective instrument for gender mainstreaming in India, as the scheme has been highly instrumental in creating increased awareness and participation among the rural women, though with variations across states. However, there are several challenges that the country may face in order to transform the NREGS as an effective instrument for gender mainstreaming. An important challenge is how to revamp the NREGS especially in states with lower women participation so as to create more work and employment opportunities resulting in increased women participation. It also calls for policies and interventions to adequately address the innate structural infirmities/problems of the NREGS that restrains women participation in the scheme in states with low levels of GWP.